Transformational leadership and organizational commitment in Korean police station: Test of second-order MLQ-6 S and OCQ - Baek, Hyunin (International journal of police science & management, 2018)
In comparison with research on the private sector, organizational commitment within the police has been rarely examined. Moreover, the leadership styles of police officials are not equal in all police studies across the world. Using data collected in 2009 from 236 Korean police officers, the purpose of this study is twofold: (a) to determine if the scale (multifactor leadership questionnaire, form 6-S [MLQ-6 S]) is applicable to police agencies internationally; and (b) to examine if leadership influences organizational commitment in law enforcement agencies. Results indicate that transformational leadership is positively linked to organizational commitment in Korean police agencies. However, the applicability of MLQ-6 S is controversial. Future research is required to examine comprehensively whether MLQ-6 S is a valid instrument for various types of organizations across the world.